Participatory selection of a maize (Zea mays L.) variety for the control of stem borers in a southeastern Nigeria location - Olaoye , G.; Ajala, S.O.; Adedeji, S.A. (2009)
Participatory varietal selection is premised on the basis that only a small percentage of varieties developed by breeders are eventually utilizedbecause farmers are left out of the selection process. Consequently a total of 275 farmers were engaged in the promotion of stem borer resistantmaize varieties in the stem borer endemic maize growing ecologies of southeastern Nigeria over a three-year period. Results obtained revealed thesuperiority of the two tested stem borer resistant varieties over the local check with one of them, Ama-TZBR-W, being more preferred by farmers.The preferred variety had better overall appeal, increased number of ears harvested and almost a four-fold increase in the number of marketablecobs when compared with the local check under the predominantly intercropping pattern practiced in the region, especially in the late croppingseason, a season with high incidence of borer infestation. Furthermore, cost-benefit analysis of the introduced technology showed a return of N35for every Naira invested by the farmer on cultivation of resistant maize variety in the study area. Nonetheless, an acceptable maize variety forcultivation in the area should in addition to having borer resistance to ensure yield stability, must also have well filled cobs and good storability,two essential attributes for food security